Neotrombicula lemni Taufflieb 1960 - Stekolnikov, Alexandr A. (Zenodo, 2018)
Neotrombicula lemni Taufflieb, 1960 Neotrombicula roubaudi var. lemni Taufflieb, 1960a: 41, pl. 6b–c. Holotype No data. Distribution Morocco (Oued Cherrat). Hosts Dipodillus campestris , Eliomys munbyanus , Lemniscomys barbarus , Mus spretus , Mustela nivalis numidica , Oryctolagus cuniculus , Passeriformes gen. sp., Rattus rattus. : Published as part of Stekolnikov, Alexandr A., 2018, Taxonomy and distribution of African chiggers (Acariformes, Trombiculidae), pp. 1-233 in European Journal of Taxonomy 395 on pages 180-181, DOI: 10.5852/ejt.2018.395, http://zenodo.org/record/3829724 : {"references": ["Taufflieb R. 1960 a. Contribution a l'etude des Trombiculidae Marocains. Description de nouvelles especes et etude d'une population de Neotrombicula. Archives de l'Institut Pasteur du Maroc 7 (1): 27 - 48."]}